Exploring the Experiences of English major students in Learning Syntax - Tatoy, Jhon Lloyd; Dinglasa, Apryll Kate; Allon, Cyra; Razon, Clyde Vic; Suarez, Aris Pet Angeli; Naparan, Genesis (Edukasiana: Jurnal Inovasi Pendidikan, 2025)
Learning English syntax is crucial for language learning. This qualitative study explores the experiences of English major students in learning syntax. The study utilized a case study approach incorporating the Sharan B. Merriam technique and data triangulation method. Through the interviews with the twenty English major students enrolled in one of the private schools in Pagadian City, categorization was utilized to categorize and identify the sub-categories that emerge. The findings reveal that students engaged in activities such as sentence structure identification, sentence tree diagramming, board activities, assessment-based activities, and interactive activities. The primary challenges included difficulty with parts of speech identification, struggle in sentence structuring, challenge in syntax rule application, and problems with complex sentence structure. To cope, students relied on memorizing and familiarizing, studying independently, collaborating in groups, and seeking guidance from teachers. While students found syntax challenging and time-consuming, they acknowledged its importance in language proficiency. The study highlights the need for supportive instructional strategies to enhance student engagement and comprehension.